Strategi Pemasaran Produk PRULink Syariah Assurance Account Pada PT. Prudental Life Assurance Cabang Kota Malang - Ernawati, Ernawati; Rifa’i, Moch. Novi (Universitas Muhammadiyah Malang, 2018)
This study aims to determine what marketing strategy implemented by PT. Prudential Life Assurance Malang City Branch in marketing PRUlink Syariah Assurance Account. Selection of PT. Prudential Life Assurance Malang Branch as a place of research is based on developments on the world of insurance, and PT. Prudential Life Assurance Malang Branch is one of the fastest growing insurance companies. This research uses descriptive research with qualitative approach, that is researcher analyze data based on information obtained from interview result, observation, and other source. While for data analysis using qualitative analysis. From the results of this study can be concluded that the marketing strategy implemented by PT. Prudential Life Assurance Malang Branch On PRUlink Syariah Product Assurance Account is using internal marketing strategy that is strategy conducted by company related to the company itself and external marketing strategy that is indirect influence where is outside of power or control of marketer.